GLOBAL SALAFISM (Perspektif Pemikiran Roel Meijer, P.hD) - Supandi, Supandi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2014)
Islam represent religion which is multidimension, so that Islam can be seen and studied in so many sides which finally studied totally (Kaffah), hence it will yield a conclusion of islam which is paradocsal, so that if conducting an mistake of approach and by mistake of read pattern to Islam, hence which in yielding exactly a product of idea of productive counter of Islam, and even frequently strengthen impression of negative face of appearance to Islam. And conducted effort and also effort rather than yielding a progress of civilization and beautify Islam face appearance which is inklussive, however progressively strengthen to jell impressively that vision of Islam face which is ekslusive and impress preacher of medial terror of the world society. Islam is very wide religion, so that in comprehending and studying about Islam world hence tend to yield a conclusion which ispardocsa lbetween which is one with other. Its meaning do a wrong near byness to Islam, hence it will yield a conclusion which is also wrong . In context of is understanding of in perpective of Roel Meijer, global movement of moslem world cleft salafism have given separate colour and pattern to Islam people, and represent khasanah properties of Islam people in perpective of understanding of them to a knowledge of religious. At least there are three specifications of it in understanding of salafism in religion, one of the other is a problem of Doctrine of religion, and then political side, and from side of jihad in salafiperspektive.